Oxygen Propagation Fronts in Porous Media Under Evaporative Conditions at the Soil/Atmosphere Interface: Lab‐Scale Experiments and Model‐Based Interpretation. Issue 6 (13th June 2022) - Ahmadi, Navid; Acocella, Michela; Fries, Elisabeth; Mosthaf, Klaus; Rolle, Massimo
Abstract: The interchange of gas components and volatile compounds between terrestrial and atmospheric compartments is critical for biogeochemical cycles and has important environmental and climate implications. In this study, we focus on oxygen and we explore the coupling between oxygen mass transfer and evaporation at the soil/atmosphere interface. We performed well‐controlled single‐phase and two‐phase laboratory experiments to determine the spatial and temporal evolution of oxygen fronts and to elucidate the coupling between mass and heat transfer in porous media with different grain sizes and under different evaporative conditions (i.e., no evaporation, natural, and enhanced evaporation). We also developed a non‐isothermal multiphase and multicomponent model to quantitatively interpret the experimental outcomes. The experiments and modeling allowed us to characterize the effects of external forcing (i.e., temperature gradients, humidity conditions) and internal factors (e.g., grain size) on the transport and distribution of oxygen in the different setups. Depth‐resolved spatial profiles and breakthrough curves of oxygen in the two‐phase experiments with evaporation are notably different from the single‐phase experiments due to the progressive gas invasion. The two‐phase experiments reveal a stepwise propagation pattern of oxygen that migrates considerably faster and penetrates deeper in the porous media in contrast to the relatively slow diffusion‐dominated transport regime in the absence of evaporation. The outcomes also show deeper and faster oxygen propagation in finer‐textured porous media under similar evaporative conditions, indicating the importance of internal factors for the distribution of the fluid phases and for the migration behavior of gas components in two‐phase systems. Key Points: Oxygen transport in porous media was investigated in single‐phase and two‐phase experiments under natural and enhanced evaporation High‐resolution spatial and temporal measurements show that water evaporation strongly impacts oxygen propagation A non‐isothermal multiphase and multicomponent model was developed and applied to interpret the experimental observations